Efeitos de relatos intermediários sobre o relato do desempenho em uma tarefa-alvo - Marcos, Marcio Alleoni (2009)
Considering the self reports of individuals about past events, the literature points out that the precision of the reports of individuals over the performance of a given task, after a certain amount of time, could be affected by what happens inbetween this given task and the report. Therefore, this study aimed to investigate: a) What is the effect of an intermediate task of similar topography matching to sample (MTS) to a target task delayed matching to sample (DMTS) on the report of the performance in this task?; b) What are the effects of report requirements that take place between the given task and the final report?; c) Would these report requirements alter the report of the given task, thus making it more accurate?; d) Would the requirement of a report that involved the construction of a similar stimulus to the comparing stimulus selected in the given task alter the final report of performance in this task?; e) Would the requirement of more than one report in a DMTS task and the final report of this responding behavior interfere the final report? Eleven college students participated in this study. They were submitted to two sessions, each with thirty-two attempts. Each cycle was composed of a given task and a report of this task. The thirty-two attempts were divided in four experimental conditions, in which were added intermediate oral reports (vocal verbal responses) and of construction (CRMTS - constructed response matching to sample). The execution of a MTS intermediate task was also requested in some conditions, being MTS the only task that had programmed responses. The results of every participant indicated that, the emission of a wrong response in a given task, foresees with great probability the error in report tasks; there were less mistakes in the given task for every participant in the second session; there is a tendency for a better performance in oral reports than in constructed reports; and the intermediate task didn t amount to a intervenient variable in the performance during the final report. It is discussed that the successive possibilility to behave in the situation to be reported and the extra stimulation provided presenting questions or the disposal of conditions for the construction of the necessary stimulus for an accurate final report. Another important question that emerged is that the requirement of an oral report might have helped a more specific identification of the stimulus peculiarity that controls the report response in the subsequent stages for the given task